Penentuan Profil Metabolit Sekunder, Aktivitas Antioksidan dan Antibakteri dari Ekstrak Biji Kurma (Phoenix dactylifera L.) Bebas Lipid - Afrizal, Afrizal; Perdana, Aditya; Suryati, Suryati (Jurnal Riset Kimia, 2022)
Dates are one of the plants that grow in the Middle East, one of them is the Golden Valley variety. Dates are usually consumed directly and can also be processed into date juice drinks. Dates refined process would produce waste in the form of date seeds are discarded and not processed into other products. This study used lipid-free Golden valley date seed extract to determine the secondary metabolite profile by using LC-MS/MS method, determining phenolic content using the Folin-Ciocalteau method, determining total flavonoids using the aluminium chloride method, determining antioxidant activity by DPPH method, and determination of antibacterial activity by the disc diffusion method. The results showed that the compounds identified from the lipid-free date seed extract were catechin-(4Î±â†’8)-catechin, bis((1S,2R,5S)-5-isopropyl-2,3-dimethylcyclo-hexyl)-2,6-dimethylpyridine-3,5-dicarboxylate, 3,5,6-trihydroxy-4',7-dimethoxyflavone, ethyl-2-amino-3-oxobutanoate, and bis(2-isopropyl-5-methylcyclohexyl)-2,6-dimethyl-1,4-dihydro-3,5-pyridine dicarboxylate. Lipid-free date seed extract contains total phenolic and flavonoid totals of 4364.704 mgGAE/100 grams of dried extract and 17200 mgQE/100 grams of dried extract. Its antioxidant activity is very strong in counteracting DPPH free radicals indicated by IC50 value of 10.1951 mg/L. Antibacterial activity shows strong inhibition of Staphylococcus aureus bacteria compared to inhibition of Escherichia coli bacteria that are categorized as weak.